Learning and quality of life in undergraduate nursing students: An exploratory study in Chile during the COVID-19 pandemic - Alejandro Almonacid-Fierro; Karla Valdebenito (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Coronavirus disease 2019 (COVID-19) is a global pandemic that has modified all social and, especially, learning instances. The purpose of this study was to determine the perception of final-year nursing students at a university in southern Chile regarding the impact of the pandemic on their learning, and consequently on their quality of life, in the context of the COVID-19 pandemic. MATERIALS AND METHODS: This is a qualitative study. The research was conducted on 14 nursing students who were selected from a university located in the province of Talca, Maule Region, Chile. Data collection was done through semi-structured interviews conducted during July and September 2021. The data were analyzed using the inductive logic of theoretical categorization; this process was assisted by the Nvivo 10 program. RESULTS: Two mega categories were generated that accounted for the nursing students' experience during the COVID-19 pandemic: objective factors category and subjective factors category. Six subcategories were derived from these two categories: free time, social relationships, learning from practice, physical exercise, eating habits, and emotional state. CONCLUSION: The research findings indicate that the students, in addition to feeling upset about not being able to do the internship, also feel that they have not been able to acquire all the knowledge necessary for their training and professional development, since the virtual classes fail to deliver adequate learning as they lack the practical component that is so important in their careers. This has repercussions in the physical, social, and psychological areas, affecting their quality of life.